2019
DOI: 10.18357/jcs00019175
|View full text |Cite
|
Sign up to set email alerts
|

Model Minority Stereotype and Racialized Habitus: Chinese Canadian Youth Struggling with Racial Discrimination at School

Abstract: This paper examines how Chinese Canadian youth struggle with the model minority stereotype and experience racial discriminationat school. Three negative connotations associated with model minority stereotype are identified, which respectively treat Chinse students as academic achievers and thus social nerds, undesirable immigrants (descendants) from the non-Western world, and targets of bullying.Drawing on Bourdieu, I elaborate on a concept of racialized habitus, particularly in relation to the model minority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Although most relevant studies are conducted by US-based researchers, discrimination is also evident in other English-speaking countries engaged in internationalization in higher education (Guo & Guo, 2017). In Canada, this social problem is concealed by an ostensible multicultural harmony, but racism is deeply rooted in Canadian history (Cui, 2019). At the beginning of the 20 th century when Eurocentrism was dominant, a textbook used in British Columbia even bluntly described Chinese or "the Yellow Race" as "some of the most backward tribes of the world [who,] as a rule, are not progressive" (Stanley, 2011, p. 108).…”
Section: Neo-racism Against International Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most relevant studies are conducted by US-based researchers, discrimination is also evident in other English-speaking countries engaged in internationalization in higher education (Guo & Guo, 2017). In Canada, this social problem is concealed by an ostensible multicultural harmony, but racism is deeply rooted in Canadian history (Cui, 2019). At the beginning of the 20 th century when Eurocentrism was dominant, a textbook used in British Columbia even bluntly described Chinese or "the Yellow Race" as "some of the most backward tribes of the world [who,] as a rule, are not progressive" (Stanley, 2011, p. 108).…”
Section: Neo-racism Against International Studentsmentioning
confidence: 99%
“…"superior" and "inferior") is systematically manifested in many educational institutions of the Western world. Cui (2019) argues that Chinese Canadian youth are often considered uncivilized, undesirable and powerless immigrants, thus prime targets of school bullying. In addition, Guo and Guo (2017) interviewed 26 international students from nine countries at a university in western Canada, and they concluded that students from Asia were more likely to encounter alienation and discrimination than those of European descent.…”
Section: Neo-racism Against International Studentsmentioning
confidence: 99%
“…As such, media representations during the 2019 Raptors playoffs repositioned the notion of an authentic Canadian and transformed Bhatia into a national icon. Scholars such as Rob Ho (2014Ho ( , 2015, Dan Cui (2019), and Gordon Pon (2000) contend that the myth of the model minority reinforces neoliberal discourses that not only stereotype Asian Canadians, but also absolve state apparatuses from creating institutional change from within. The model minority discourse assumes that racial minorities can move past the historical and material conditions of settler-colonial practices and achieve the Canadian dream.…”
Section: "I Hope They See Diversity and Loyalty" (Tim Hortons 2019): ...mentioning
confidence: 99%
“…Seeing as how flexible citizenship and economic docility are both, in part, strategies for minimizing the harms of discrimination, the common feature between those environments and my own could indeed be discrimination. Cui's (2015;2019) studies of Chinese Canadian youth reveal further examples of these kinds of coping mechanisms amongst not just skilled migrant children, but descendants of migrants more generally. Some of her participants tried to avoid appearing studious in front of white peers in fear of appearing foreign.…”
Section: Lifeworld Practicesmentioning
confidence: 99%
“…It has been argued, both in the Canadian and American contexts, that the Asian diaspora has to contend with visibility gaps in both public and academic discourse (Museus & Kiang 2009;Cui 2019;Mu & Pang 2019). In much of the existing literature that criticizes this visibility gap, 'model minority' stereotypes are said to be the culprit.…”
Section: Visibility Gapsmentioning
confidence: 99%